Exploration and Validation of Behavioral Pain Measures and Physiological Pain Measures Factor Structure Extracted From the Pain Assessment Tool Item Scores for Infants Admitted to Neonatal Intensive Care. Issue 6 (June 2021) - Ilhan, Emre; Pacey, Verity; Brown, Laura; Spence, Kaye; Galea, Claire; Adams, Roger; Hush, Julia M.
Abstract : Objective: The objective of the study was to explore and then validate the factor structure of the Pain Assessment Tool (PAT). Materials and Methods: A retrospective medical record review was performed of all infants who were admitted to a neonatal intensive care unit between 2008 and 2018 and had 1 PAT assessment (n=2111). Scores on items of the PAT were collected. Infants were randomized to either the principal component analysis (n=1100) to explore the factor structure or confirmatory factor analysis (n=1011). Results: Infants in the 2 samples were demographically comparable. A 2-factor model, consisting of factors Behavioral and Physiological Pain Measures, was extracted, explaining 39.8% of the total variance. There was a low interfactor correlation ( r =0.12), and both Behavioral ( r =0.59) and Physiological Pain ( r =0.37) Measures factor scores were correlated with nurses' perception of pain scores. When the frequencies in the gestational age at birth categories were compared between upper and lower quartile score infants, there was more with pain at preterm than at term (χ 2 (3)=44.9, P <0.001) for the Physiological Pain Measures factor, whereas Behavioral Pain Measures frequency was higher at term than at preterm (χ 2 (3)=8.1, P <0.043). A similar pattern was observed for postmenstrual age at assessment categories: Behavioral Pain Measures (χ 2 (3)=41.8, P <0.001) Physiological Pain Measures (χ 2 (3)=46.1, P <0.001). The 2-factor correlated model performed better at explaining the observed variances: (χ 2 (13)=41.6, P <0.001) compared with rival models. Discussion: The PAT assesses both Behavioral Pain and Physiological Pain Measures, and these dimensions need to be considered separately when assessing pain in infants in the neonatal intensive care unit. Behavioral item scores may be insufficient for detecting pain in premature infants if used alone.